2021
DOI: 10.3390/genes12122022
|View full text |Cite
|
Sign up to set email alerts
|

NAPRT Expression Regulation Mechanisms: Novel Functions Predicted by a Bioinformatics Approach

Abstract: The nicotinate phosphoribosyltransferase (NAPRT) gene has gained relevance in the research of cancer therapeutic strategies due to its main role as a NAD biosynthetic enzyme. NAD metabolism is an attractive target for the development of anti-cancer therapies, given the high energy requirements of proliferating cancer cells and NAD-dependent signaling. A few studies have shown that NAPRT expression varies in different cancer types, making it imperative to assess NAPRT expression and functionality status prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…NAPRT displays marked tissue and tumor specificity in terms of expression and its regulation mechanisms and is mostly present in several catabolic healthy mammalian tissues including the heart, kidney, liver, and small intestine [ 19 , 25 , 30 , 31 , 32 , 33 ]. In tissues that express the NAPRT protein, NA is the preferred precursor of NAD.…”
Section: Introductionmentioning
confidence: 99%
“…NAPRT displays marked tissue and tumor specificity in terms of expression and its regulation mechanisms and is mostly present in several catabolic healthy mammalian tissues including the heart, kidney, liver, and small intestine [ 19 , 25 , 30 , 31 , 32 , 33 ]. In tissues that express the NAPRT protein, NA is the preferred precursor of NAD.…”
Section: Introductionmentioning
confidence: 99%
“…The benzimidazole ring is ionized at physiological pH and engages Asp320 A with a salt bridge and H-bonds. Asp320 A is indirectly connected through a tight H-bonding network to Arg318 A , a residue implicated in catalysis through mutagenesis [ 27 , 28 ]. Intriguingly, Arg318 is also perturbed by two reported inhibitors ( 10 and 12 in Figure 2 ) that share similar chemical moieties with our inhibitory scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that NAMPT and NAD + are frequently upregulated in several human malignancies and play key roles in the development, progression, and recurrence of cancer (Lucena-Cacace et al, 2018 ; Zhang et al, 2019 ). Furthermore, unlike tumor cells, which mostly depend on NAMPT, normal cells can synthesize NAD + through other biosynthetic pathways, such as nicotinic acid phosphoribosyltransferase (NAPRT) (Duarte-Pereira et al, 2021 ). NAMPT and NAD + not only affect tumor metabolism but also affect the tumor immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%